2016
DOI: 10.1161/circinterventions.115.003326
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation Compared With Surgical Aortic Valve Replacement in Low-Risk Patients

Abstract: Background-The proven efficacy of transcatheter aortic valve implantation (TAVI) in high-risk patients is leading to the expansion of its indications toward lower-risk patients. However, this shift is not supported by meaningful evidence of its benefit over surgical aortic valve replacement (SAVR). This analysis aims to describe outcomes of TAVI versus SAVR in low-risk patients. Methods and Results-We compared the outcome after TAVI and SAVR of low-risk patients (European System for CardiacOperative Risk Evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 23 publications
7
78
0
Order By: Relevance
“…As Rosato et al 12 intimate in their conclusions, there are currently insufficient data to justify an expansion of TAVR to low-risk subgroups. Although their findings would suggest that such patients fare worse with TAVR than SAVR in terms of both mid-and longterm outcomes (ie, survival and major adverse cardiovascular and cerebral events), their mortality rates after TAVR seem disproportionately high compared with other recent studies, especially in light of the low-risk study population.…”
Section: See Article By Rosato Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…As Rosato et al 12 intimate in their conclusions, there are currently insufficient data to justify an expansion of TAVR to low-risk subgroups. Although their findings would suggest that such patients fare worse with TAVR than SAVR in terms of both mid-and longterm outcomes (ie, survival and major adverse cardiovascular and cerebral events), their mortality rates after TAVR seem disproportionately high compared with other recent studies, especially in light of the low-risk study population.…”
Section: See Article By Rosato Et Almentioning
confidence: 99%
“…The study also demonstrated that rates of stroke (4.6%) and moderate or severe aortic regurgitation (1.5%) had improved with the Sapien 3 device relative to the Sapien XT. 12 The OBSERVANT study is a large prospective observational cohort that enrolled patients undergoing transcatheter and surgical AVR at 93 Italian centers for an 18-month time period and coordinated by the Italian National Institute of Health. The original aim of OBSERVANT was to characterize the comparative effectiveness between these treatment modalities in a real-world setting.…”
mentioning
confidence: 99%
“…Patient background, clinical findings and blood test results were retrieved from electronic medical records (EMRs) and anesthesia charts. Data were collected for age, gender, European System for Cardiac Operative Risk Evaluation II (Euro II) score [5], Logistic Euro (LogEuro) score, Society of Thoracic Surgery (STS) score [6], albumin level [7], renal function based on estimated glomerular filtration rate (eGFR), hypertension, diabetes, dyslipidemia, coronary artery disease(CAD) and percutaneous coronary intervention (PCI), chronic obstructive pulmonary disease (COPD), and New York Heart Association (NYHA) classification.…”
Section: Patient Populationmentioning
confidence: 99%
“…Results from the PARTNERS II trial conclude that in intermediate-risk patients, TAVI was similar to surgical AVR with respect to the primary end point of death or disabling stroke 15. Rosato et al 16 have recently reported in patients with low operative risk a significantly better 3-year survival and freedom from major cardiac and cerebrovascular in patients undergoing surgical AVR compared with TAVI. In addition, controversy exists on the cost-effectiveness of TAVI 17.…”
Section: Introductionmentioning
confidence: 99%